THE USE OF HOT POTATOES IN TEACHING DESCRIPTIVE TEXTS TO EFL SECONDARY SCHOOL STUDENTS - Pariyanto Pariyanto; Atik Herawati (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2020)
Abstract: The present study explored the effectiveness of teaching descriptive texts through Hot Potatoes to English as a foreign language (EFL) secondary school students and their perception of learning using this media. 31 junior high school students in Year VII participated in the study. A quasi-experimental with pretest -posttest design and a qualitative descriptive design were used in this inquiry. The results indicated that the use of Hot Potatoes to teach descriptive text to secondary school students was effective, pretest (M=74.74, SD=10.23) posttest (M=89.55, SD=5.96) t(30)=-10.97, p=.000 and that it was perceived to be useful and interesting teaching media by the students. These suggest that Hot Potatoes has potential benefits when incorporated into teaching of reading where the teachers can take it into account to be employed in their reading class.